Strategi Optimalisasi Administrasi Ekspor Impor dalam Mendukung Pertumbuhan Ekonomi Regional Provinsi Lampung - Suryani, Suryani (Business Perspective Journal, 2024)
Import-export administration plays an important role in supporting smooth international trade, which in turn contributes to regional economic growth. This study aims to analyze the optimization strategy of import-export administration in Lampung Province as one of the strategic regions in Indonesia's international trade. The research method used is a descriptive qualitative approach with secondary data analysis from relevant agencies, including the Central Statistics Agency (BPS), the Office of Industry and Trade, and Bandar Lampung Customs Office. The results show that the main obstacles in import-export administration in Lampung Province include the complexity of bureaucratic procedures, limited infrastructure, and low utilization of digital technology by business actors. To overcome these obstacles, this study recommends optimization strategies that include: (1) digitizing the administration system through an integrated platform; (2) increasing the capacity of human resources through competency-based training; (3) simplifying regulations and harmonizing policies across sectors; and (4) strengthening supporting infrastructure, especially ports and logistics transportation. The implementation of this strategy is expected to improve the efficiency and transparency of administrative processes, accelerate the flow of goods, and improve the competitiveness of import-export in Lampung Province. Thus, optimizing import-export administration not only supports regional economic growth, but also contributes to Indonesia's position in international trade. Keywords: import-export administration, optimization, economic growth, Lampung Province, international trade